Coincidences of multiple fibre-preserving maps - Mendes Monis, Thaís Fernanda [UNESP]; Silva, Weslem Liberato (Elsevier, 2021)
In this paper we study the following problem: given X↪M→B and Y↪N→B smooth fibre bundles over B and f1,…,fk:M→N fibre-preserving maps, is it possible to deform (f1,…,fk)∼(f1′,…,fk′) via a fibrewise homotopy over B such that the set of coincidence points of f1′,…,fk′:M→N is empty? We study this question making use of obstruction theory.
Keywords: Coincidence; Fibre-preserving maps; Obstruction theory